Making the Invisible Visible: The Role of the Cuban Socio-cultural Contexts in Fostering Transformative Learning - James West; John Dirkx (Adult Education Research Conference, 2019)
In this study, we sought to develop a deeper understanding of how socio-cultural and socio-material contexts contributed to intercultural and transformative learning on a short-term study abroad program in Cuba.
Keywords: education abroad; transformative learning